Team dynamics over time - Salas, Eduardo; Vessey, William B.; Landon, Lauren B. (Emerald Publishing Limited, 2017)
This volume addresses the need to focus on temporal adaptations of teams. Modern organizations have been relying on teams more often to cope with the changing economic and technological climate. An increase in the use of teams has led to more team research throughout the fields of cognitive science, human factors, organizational psychology, assessment, and behavioral science. How teams grow and change is important for their performance and their members' satisfaction with their work; therefore, the attention that this book lends to teams' temporal factors is much deserved. Editors Eduardo Salas, Lauren B. Landon and William B. Vessey have gathered some of the best and brightest team researchers to contribute to this book. The various chapters offer readers background information, temporal measurement tools, and implications for research and practice. The book covers such interesting perspectives as team leadership, trust, cultural implications, and temporal implications in long-duration, extreme situations, including space exploration. This book serves as a resource to researchers who study teams, managers who lead teams, and those who work in teams.
Includes index.
Keywords: Corporate culture.; Corporate governance.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books